Student Assessment of Online Learning of MKWK Indonesian Language In The New Normal Era - Defina Defina (Jurnal Pendidikan Bahasa dan Sastra, 2023)
The purpose of this study is to describe student assessment of the implementation of this lecture. This research is descriptive research with data collection techniques through Google Forms. The respondents were IPB Vocational School students for the 2021/2022 academic year. The number of students who filled out the questionnaire was 92. As a result, in blended learning, students preferred the offline one; the obstacles faced when online are internet connections and other supporting facilities, while offline is the distance traveled; the material that should be given offline is writing and speaking, while online is PUEBI; writing material is material that is difficult to understand both online and offline; boredom in learning caused by lecturer teaching techniques; activities that are carried out when there are obstacles and boredom vary. This research aims to find the causes of students' constraints and boredom in blended learning.